2012
DOI: 10.1002/ajpa.22066
|View full text |Cite
|
Sign up to set email alerts
|

Scurvy in the Great Irish Famine: Evidence of vitamin C deficiency from a mid‐19th century skeletal population

Abstract: Scurvy has increasingly been recognized in archaeological populations since the 1980s but this study represents the first examination of the paleopathological findings of scurvy in a known famine population. The Great Famine (1845–1852) was a watershed in Irish history and resulted in the death of one million people and the mass emigration of just as many. It was initiated by a blight which completely wiped out the potato—virtually the only source of food for the poor of Ireland. This led to mass starvation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 52 publications
7
95
0
2
Order By: Relevance
“…48–49) is a possible noncarious‐related cause of tooth loss of relevance for this population sample. This condition has previously been diagnosed in high rates in these individuals (Geber & Murphy, 2012). A chi‐square test, however, failed to detect a difference in the frequency of tooth loss between nonscorbutic and scorbutic (possible, probable, and definite diagnoses) individuals for both anterior (χ 2 (1) = 0.140, p  = .708) and posterior (χ 2 (1) = 0.005, p  = .943) dentitions.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…48–49) is a possible noncarious‐related cause of tooth loss of relevance for this population sample. This condition has previously been diagnosed in high rates in these individuals (Geber & Murphy, 2012). A chi‐square test, however, failed to detect a difference in the frequency of tooth loss between nonscorbutic and scorbutic (possible, probable, and definite diagnoses) individuals for both anterior (χ 2 (1) = 0.140, p  = .708) and posterior (χ 2 (1) = 0.005, p  = .943) dentitions.…”
Section: Methodsmentioning
confidence: 90%
“…A previous paleopathological study of the Kilkenny population sample has suggested that Vitamin C deficiency compromised the ability of these individuals to combat infectious diseases and greatly influenced their risk of death when entering the overcrowded workhouse institution. The mass mortality in this environment was mainly the result of infectious so‐called “famine diseases” such as typhus, typhoid fever and cholera (Geber & Murphy, 2012). The inclusion of periodontal disease, caused by lifestyle factors, as a potential contributor to the physical demise of a large proportion of the Irish population during the mid‐nineteenth century, further highlights the complexity and variability of the human experience of the Great Irish Famine.…”
Section: Discussionmentioning
confidence: 99%
“…However, its application is not universally practical considering problems with preservation and completeness. Although interpretative caution is needed in order to avoid over diagnosis in paleopathology, the Ortner suite and other proposed hemorrhagic lesions (e.g., new bone around the foramen rotundum; Geber & Murphy, 2012) are logical from an anatomical and pathophysiological standpoint and their continued use in paleopathological research is tenable. However, as discussed in section five, the diagnostic weight attributed to these lesions should be explicitly justified and continually reassessed in paleopathological work.…”
Section: Critiques Of the Ortner Criteriamentioning
confidence: 99%
“…Subperiosteal new bone on the shafts of long bones, as well as evidence of hemarthrosis, has been radiographically observed in adults with this disease, but these features also occur in a number of other pathological conditions, including trauma and infectious disease (Jaffe, 1972; Joffe, 1961). As chronic hemorrhage occurs in both scorbutic adults and children, the macroscopic lesions reported by Ortner and others can theoretically be applied to adult individuals and well as subadults (Crandall & Klaus, 2014; e.g., Buckley et al, 2014; Geber & Murphy, 2012). Jaffe (1972) reports that autopsy findings of adults with scurvy include bloody discoloration of muscle bellies and attachments, which lends clinical credibility to this argument (Jaffe, 1972, p. 454).…”
Section: Adult Scurvy: a Diagnostic Conundrummentioning
confidence: 99%
See 1 more Smart Citation